2003
DOI: 10.1021/ic034473t
|View full text |Cite
|
Sign up to set email alerts
|

Five- to Six-Coordination in (Nitrosyl)iron(II) Porphyrinates:  Effects of Binding the Sixth Ligand

Abstract: We report structural and spectroscopic data for a series of six-coordinate (nitrosyl)iron(II) porphyrinates. The structures of three tetraphenylporphyrin complexes [Fe(TPP)(NO)(L)], where L = 4-(dimethylamino)pyridine, 1-methylimidazole, 4-methylpiperidine, are reported here to a high degree of precision and allow observation of several previously unobserved structural features. The tight range of bonding parameters for the [FeNO] moiety for these three complexes suggests a canonical representation for six-coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

41
123
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(165 citation statements)
references
References 50 publications
(81 reference statements)
41
123
0
Order By: Relevance
“…Previous density functional calculations gave comparable results for 6-coordinate porphyrins (23), whereas Hartee-Fock calculations do not predict a bond between the iron and bound NO, but instead give values that are more consistent with a van der Waal's complex. The x-ray data of the 5C-NO-porphyrin at 295 K (47) revealed that the iron is displaced by 0.21 Å from the heme center toward NO, a value very close to those obtained by DFT calculations (Table 2). On the contrary the heme has a more planar configuration for 6C-NO porphyrin.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…Previous density functional calculations gave comparable results for 6-coordinate porphyrins (23), whereas Hartee-Fock calculations do not predict a bond between the iron and bound NO, but instead give values that are more consistent with a van der Waal's complex. The x-ray data of the 5C-NO-porphyrin at 295 K (47) revealed that the iron is displaced by 0.21 Å from the heme center toward NO, a value very close to those obtained by DFT calculations (Table 2). On the contrary the heme has a more planar configuration for 6C-NO porphyrin.…”
supporting
confidence: 84%
“…The Fe-N-O bonds are bent for both 5-and 6-coordinate calculations and x-ray structures with an angle in the range 139 -144° (Table 2), which is within 5°of the experimental angle in all cases (47). As expected, the angle Fe-N-O is higher for the calculated model than for Mb-NO (close to 111°; see Ref.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…4), which produces more confidence in their refined positions. The geometry of the NO-ligated heme in the 0.95 Å ferrous nitrosyl blackfin tuna myoglobin structure is very similar to that observed in both small molecule crystal structures of model compounds (45) and in high level theoretical calculations (46), with a Fe-NO bond length of 1.74 Å and a Fe-N-O angle of 134°( Table 2). The only other atomic resolution protein crystal structures that feature a nitric oxide-and histidine-ligated heme are of the nitrophorin 4 (NP4) protein from Rhodnius prolixus, a non-globin heme protein.…”
Section: Production and Stability Of S-nitrosylated Blackfin Tunasupporting
confidence: 67%
“…This has been further demonstrated in a series of temperature-dependent crystal structures and IR investigation [87]. There are other effects on the structure around iron on the addition of the sixth ligand that have been summarized in references [87][88][89]. We have also characterized additional iron(III) species, espcially six-coordinate species and the original references include the following [90][91][92][93][94].…”
Section: Discussionmentioning
confidence: 76%